2019
DOI: 10.21608/ejoh.2019.6279.1087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium and Boron on Growth, Fruit Setting and Yield of Hot Pepper (Capsicum annuum L.)

Abstract: to study the response of hot pepper plant (Capsicum annuum L.) cv. Hot Chili growth, fruit setting, yield and some biochemical constituents linked with the yield and quality characteristics to foliar spraying with calcium chloride at 0, 1000 and 2000 ppm, boric acid at 0, 200 and 400 ppm and their combinations. Results indicated that all foliar applications of calcium chloride and boric acid treatments individual or in combination markedly increased the vegetative growth characteristics, fruit setting percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Regarding, enhanced the vegetative growth and yield traits of carrot in the present study by using boron foliar application at 500 ppm were similar with results of Abou EL-Yazied and Mady, 2012 on broad bean, El-Dissoky and Abdel-Kadar, 2013 on potato, Gondim et al, 2015 on beet and tomato plants and Salim et al 2019 on hot pepper. Synergistic effect of B foliar spray which improved the plant growth and yield may be due to increase the photosynthetic pigments and endogenous auxins and cytokinins (Abou EL-Yazied and Mady, 2012).…”
Section: The Vegetative Growth and Storage Roots Yieldsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding, enhanced the vegetative growth and yield traits of carrot in the present study by using boron foliar application at 500 ppm were similar with results of Abou EL-Yazied and Mady, 2012 on broad bean, El-Dissoky and Abdel-Kadar, 2013 on potato, Gondim et al, 2015 on beet and tomato plants and Salim et al 2019 on hot pepper. Synergistic effect of B foliar spray which improved the plant growth and yield may be due to increase the photosynthetic pigments and endogenous auxins and cytokinins (Abou EL-Yazied and Mady, 2012).…”
Section: The Vegetative Growth and Storage Roots Yieldsupporting
confidence: 90%
“…Therefore, adding B increased the P, K, Mg, carotenes and vitamin C concentrations in storage roots of carrot (Singh et al, 2012). Also, foliar spray with boric acid at levels 200 or 400 ppm increased concentrations of N, P, and K in the leaf and carotenoids and vitamin C of hot pepper fruit (Salim et al, 2019). Furthermore, Day and Aasim (2020) reported that, B has synergistic impacts on photosynthetic pigments, P, N, K, Zn, Fe, and Cu uptake and translocation in plants.…”
Section: Storage Root Qualitymentioning
confidence: 91%
See 1 more Smart Citation
“…For this reason, Fernández et al (2013) suggested that the supply of these nutrients should be done via foliar application in the flowering or post-flowering phase in order to increase seed yield and quality. Besides this, calcium and boron are nutrients of great importance in germination of pollen, pollen tube growth, flower fixation and, therefore, in seed production (Salim et al, 2019), and foliar application permits to control the quantity of the nutrients and the specific period of plant growth (Niu et al, 2020).…”
Section: Resumo Aplicação Foliar De Cálcio E Boro Na Produção E Quali...mentioning
confidence: 99%
“…Boron is the micronutrient most accumulated by pepper fruits and, in adequate amounts, it can favor the development and production of fruits and its deficiency can lead to floral abortion and poor seed formation (Mello et al, 2002). Zeist et al (2018) and Salim et al (2019) related greater fruit yield in pepper plants with foliar application of calcium and boron, isolated or combined, but they did not evaluate seed production.…”
Section: Palavras-chavementioning
confidence: 99%